EFEKTIFITAS PENGADILAN NIAGA DALAM MENYELESAIKAN SENGKETA HAK CIPTA BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2002 - ASRIL, FERRY (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2017)
The existence of the Commercial Court has been recognized by the Indonesian legalsystem and is seen as part of the existing judicial system. The establishment of a CommercialCourt currently located in 5 (five) major cities in Indonesia, is intended to assist in the smoothprocess of dispute resolution of Copyright. But in fact, due to various factors and reasons, notall copyright disputes can be handled by the Commercial Court. The first Commercial Courtestablished was the Central Jakarta Commercial Court. Furthermore, based on PresidentialDecree No. 97 of 1999, August 18, 1998, established Commercial Court in Makassar,Surabaya, Medan and Semarang. The basic principles adopted in commercial court are asfollows: continuity, good trials, good decisions and good archives.The main problem in this research is how the procedures and procedures for thesettlement of copyright according to Law Number 19 Year 2002 and What are the Weaknessof Commercial Court in handling the Copyright dispute pursuant to Law Number 19Year2002.This type of research is combination research, that is With document studies,surveys, and document studies is to study copyrighted documents handled by Jakarta andMedan commercial courts (within the time limit of which authors have authored themselves)Procedures and procedures for the settlement of copyrights under the Law Number 19 Year2002 is generally the same as litigation in the District Court but there is a special procedure inwhich the procedure of handling the case so short that has been set time in Law Number 19Year 2002 and the decision on this case can only be requested cassation.What is the weakness of the Commercial Court in handling the Copyright disputebased on Law Number 19 Year 2002 is caused by several factors including the following: Thejustice seekers themselves, the Judge who resolved the case, The lack of trade court inIndonesia, The amount of cost required For litigation in commercial courts. Besides, theweakness of the Commercial Court in dealing with copyright disputes is the limited number ofcommercial courts, so the judges are also very poor, as not all judges can be subjected toCommercial Court judges. Besides the human resource factor, where the Commercial Courtjudges do not all have special expertise on copyright, this makes it difficult to make decisionsthat really fit the public sense of justice.Keywords: Effectivity of Commercial Court, Copyright Dispute and LawNumber 19 Year 2002